Wave propagation in fluid-saturated nanoporous media: Upscaling molecular mechanics into continuum-level description - Alan Sam; Benoit Coasne; Rodolfo Venegas (Proceedings of the National Academy of Sciences, 2026)
Understanding how mechanical, thermodynamic, and acoustic properties emerge in fluid-saturated nanoporous materials remains a major challenge due to the breakdown of classical continuum assumptions at molecular length scales. Here, we present a multiscale framework that extends linear chemo-poroelasticity theory to describe the coupled response of nanoporous solids and confined fluids to mechanical wave excitation. The effective poromechanical parameters—elasticity and stress-chemistry coupling tensors, scalar chemistry modulus, and fluid mobility tensor—are computed from atomistic simulations of methane adsorption and transport in a prototypical zeolite. These simulation-informed parameters are then embedded in a continuum model of mechanical wave propagation. This integrated approach enables the prediction of the effective wave speeds and attenuation as a function of frequency, fluid loading, and nanopore-scale structure. The methodology provides a physically grounded path for linking molecular interactions to macroscopic acoustic and elastic response. In turn, this framework offers opportunities for designing nanoporous materials with tailored transport, mechanical, and acoustical properties—particularly in the emerging field of nanoscale acoustics.